Analisis Piutang pada PT Pos Indonesia Regional V Surabaya - Hayati Sivak; Anita Handayani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to explore the management of receivables at PT Pos Indonesia Regional V Surabaya, focusing on the control of problematic receivables, credit analysis, and collection procedures. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document reviews, including aging reports of receivables. The results indicate that 74% of receivables are over six months old, reflecting inefficiencies in credit risk assessment and collection practices. To reduce problematic receivables, the implementation of more effective management strategies is recommended, such as credit feasibility analysis, a more structured credit sales policy, and strengthening internal controls. These steps are expected to stabilize cash flow and improve the quality of service to customers.